2016
DOI: 10.1038/labinvest.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen promotes healing in a bacterial LPS model of delayed cutaneous wound repair

Abstract: Wound infection is a major clinical problem, yet understanding of bacterial host interactions in the skin remains limited. Microbe-derived molecules, known as pathogen-associated molecular patterns, are recognised in barrier tissues by pattern-recognition receptors. In particular, the pathogen-associated molecular pattern, lipopolysaccharide (LPS), a component of microbial cell walls and a specific ligand for Toll-like receptor 4, has been widely used to mimic systemic and local infection across a range of tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 76 publications
9
39
0
1
Order By: Relevance
“…Under our experimental conditions, the K m value for nitrocefin measured for full-length KPC-2 was determined as 36.0 mm. [26,28,29] The K i values for derivatives 1-5 were obtained from the IC 50 values as per competitive inhibition (Cheng-Prusoff equation), in agreement with the inhibition patterns in this series of compounds and with experiments investigating the effect of increasings ubstrate concentrations (Table 1).…”
Section: Bl Inhibition Studies and Susceptibility Assayssupporting
confidence: 75%
See 2 more Smart Citations
“…Under our experimental conditions, the K m value for nitrocefin measured for full-length KPC-2 was determined as 36.0 mm. [26,28,29] The K i values for derivatives 1-5 were obtained from the IC 50 values as per competitive inhibition (Cheng-Prusoff equation), in agreement with the inhibition patterns in this series of compounds and with experiments investigating the effect of increasings ubstrate concentrations (Table 1).…”
Section: Bl Inhibition Studies and Susceptibility Assayssupporting
confidence: 75%
“…To investigate the inhibitory activity of the phenylboronic acid derivatives, full‐length KPC‐2 and KPC‐2 with a C‐terminal deletion were overexpressed and purified in a single chromatographic step to yield more than 150 mg of protein per liter of culture, with a purity degree higher than 99 %. Under our experimental conditions, the K m value for nitrocefin measured for full‐length KPC‐2 was determined as 36.0 μ m …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, promotion of cell repairing/healing process is important for renoprotection and stone prevention. Several previous studies have demonstrated the effects of estrogen on cell migration and tissue healing that involved many signaling pathways, e.g., MAPK and PI3K pathways . In concordance, our proteomics data showed that mitogen‐activated protein kinase 1 (MAPK1) (spot #339) was significantly increased in the estrogen‐treated cells.…”
Section: Discussionsupporting
confidence: 88%
“…For example, TLR4 plays an essential role in early skin wound healing [7]. HMGB1, an endogenous ligand of TLR4, accelerates wound healing [8, 9], whereas a bacterial lipopolysaccharide, an exogenous ligand of TLR4, delayed cutaneous wound healing [10]. Activation of TLR9 by CpG oligodeoxynucleotides accelerates wound healing [11].…”
Section: Introductionmentioning
confidence: 99%